2001
DOI: 10.1002/1097-0142(20010415)91:8<1557::aid-cncr1165>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic features and outcome in patients with diffuse large B-cell lymphoma who do not achieve a complete response to first-line regimens

Abstract: BACKGROUND The current study was conducted to analyze the outcome and prognostic factors of patients with diffuse large B‐cell lymphoma (DLCL) who did not achieve a complete response (CR) to first‐line treatment. METHODS The current study was comprised of 83 patients (43 males and 40 females with a median age of 62 years) who did not achieve a CR (58 of whom had primary refractory disease and 25 of whom achieved a partial response) with initial treatment (doxorubicin‐containing regimens in 87% of cases) from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…In another report, progressive disease during treatment was experienced by 22 and 9.5 % patients after CHOP and R-CHOP, respectively [1]. The degree of response was found to be the only significant variable predictive of survival, with a 2-year survival rate of 4 % for primary refractory and 40 % for patients who achieved a partial response to CHOP-like chemotherapy [8].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In another report, progressive disease during treatment was experienced by 22 and 9.5 % patients after CHOP and R-CHOP, respectively [1]. The degree of response was found to be the only significant variable predictive of survival, with a 2-year survival rate of 4 % for primary refractory and 40 % for patients who achieved a partial response to CHOP-like chemotherapy [8].…”
Section: Discussionmentioning
confidence: 94%
“…This paradigm is assumed to remain valid with R-CHOP treatment. In one prior retrospective study in the prerituximab treatment era, primary refractory disease was noted in 17 % of 236 patients with DLBCL with a resultant median OS of 10 months [8]. In another report, progressive disease during treatment was experienced by 22 and 9.5 % patients after CHOP and R-CHOP, respectively [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, in other retrospective analyses focusing on patients not in CR after first line, before rituximab era, fully refractory patients had a significantly worse OS compared with patients who had a partial response after first line [29,30]. The prognostic value of time to relapse has also been evaluated in selected patients rescued with chemotherapy followed by ASCT.…”
Section: Outcomementioning
confidence: 99%
“…Villela et al reported on the outcome of patients who failed to achieve a complete remission with first-line therapy [10]. Their patient population does not match our patient population entirely as it was not restricted to elderly patients, but patients with refractory disease also had a very poor outcome.…”
Section: Discussionmentioning
confidence: 82%